Tinjauan Perbandingan Rencana Anggaran Biaya Dan Waktu Pelaksanaan Pembangunan Gedung Fakultas Kedokteran Universitas Bosowa Makassar - Umar, Zukry; Abduh, Muhammad Natsir; Mullyani, Savitri Prasandi (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
In the world of construction, project management has an important role such as determining the budget planning and implementation time, its function is to find out how much budget is needed and how long it takes. In order to facilitate implementation in the field. In this study there are two methods used, namely the method based on the Regulation of the Minister of Public Works and Public Housing Number 28 of 2016 and the method based on the Regulation of the Minister of Public Works and Public Housing Number 1 of 2022. This study is a re-examination of the actual calculation using the method Regulation of the minister of public works and public housing number 28 of 2016. From the results of the comparison of the budget plan for the construction of the Faculty of Medicine, University of Bosowa Makassar, which has been made by PT. Seven Guardians of (Rp. 24.008.000.000) with a duration of work for 483 days and made by the author of Rp. 23. 511. 000 000. with a duration of work for 434 days.